2012
DOI: 10.1371/journal.pone.0036683
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Acetylcholinesterase Enhances Neurite Outgrowth of Rat R28 Cells Through Interaction With Laminin-1

Abstract: The enzyme acetylcholinesterase (AChE) terminates synaptic transmission at cholinergic synapses by hydrolyzing the neurotransmitter acetylcholine, but can also exert ‘non-classical’, morpho-regulatory effects on developing neurons such as stimulation of neurite outgrowth. Here, we investigated the role of AChE binding to laminin-1 on the regulation of neurite outgrowth by using cell culture, immunocytochemistry, and molecular biological approaches. To explore the role of AChE, we examined fiber growth of cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 65 publications
(74 reference statements)
2
11
0
2
Order By: Relevance
“…This possibility intrigued us, since AchE is known to bind to laminin4344 and can enhance cell adhesion and neurite outgrowth454647. A synergistic effect of laminin and AchE on neurite outgrowth has also been demonstrated in the R28 neuronal cell line48. These functions are attributed to the peripheral anionic site are unrelated to AchE enzymatic activity4649.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility intrigued us, since AchE is known to bind to laminin4344 and can enhance cell adhesion and neurite outgrowth454647. A synergistic effect of laminin and AchE on neurite outgrowth has also been demonstrated in the R28 neuronal cell line48. These functions are attributed to the peripheral anionic site are unrelated to AchE enzymatic activity4649.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these data suggest that ventromedial neurons, such as those that co-express Djchat and the Djche genes, may be important for formation, patterning, and maintenance of the planarian brain. Studies in several animal models and cell culture systems have suggested that AChE may have morphogenic functions during neurodevelopment, which may or may not depend on catalysis of ACh (Bigbee et al 2000; Biagioni et al 2000; Paraoanu et al 2006; Yang et al 2008; Sperling et al 2012; Layer et al 2013). Consistent with the possibility that DjChE activity may regulate planarian brain formation, we previously found that subchronic exposure to high concentrations of the OP chlorpyrifos led to decreased brain size in regenerating but not full worms (Hagstrom et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…To place this in context, R28, a sister cell line to Mocha, is a rat retinal precursor cell line established over 20 years ago also using the same 12S E1A immortalization technique (Seigel, 1996). R28 cells, like Mocha cells, do not express all markers of the mature cell type (Seigel et al, 2004), but can respond to some conditions that promote differentiation (Sperling, et al, 2012). R28 cells have been utilized in hundreds of studies, both in vitro and in vivo as a model for cytotoxicity (Patil, et al, 2009), differentiation (Sperling et al, 2012), transplantation (Seigel, et al, 1998) and retinal cell behavior (Uddin, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…R28 cells, like Mocha cells, do not express all markers of the mature cell type (Seigel et al, 2004), but can respond to some conditions that promote differentiation (Sperling, et al, 2012). R28 cells have been utilized in hundreds of studies, both in vitro and in vivo as a model for cytotoxicity (Patil, et al, 2009), differentiation (Sperling et al, 2012), transplantation (Seigel, et al, 1998) and retinal cell behavior (Uddin, et al, 2016). We anticipate that Mocha cells will show similar utility in studies relating to the inner ear as an immortalized cell line.…”
Section: Discussionmentioning
confidence: 99%